Performance Analysis of Shari’ah Cooperative Financial Statements at The Hajj Bond of The Arwaniyyah Foundation (IHYA) in Kudus - Estiningtyastuti; Eko Budi Utomo (International Journal of Seocology, 2022)
The Purpose of study was to asses the work of monetary report at Koperasi Syariah “IHYA” Kudus According to Ratio Liquidity Analysis and Leverage Ratio. This study need secondary data such as dokumantation or the note related with studys object. This study was done to the work of monetary report at Koperasi Syariah “IHYA” Kudus on 2018-2020. The researcher used Liquidity Ratio, Leverage Ratio and Profitability Ratio. The work of monetary report at Koperasi Syariah “IHYA” Kudus that was assessed with Liquidity Ratio and Profitability Ratio, was not fulfil monetary ratio obtained because the value was lower than minimum standart for cooperative. Leverage Ratio cooperative was fulfil the monetary report obtained because it was higher than minimum standart value. Generally, the work of Koperasi Syariah “IHYA”According to Liquidity Ratio, Leverage Ratio and Profitability Ratio, was less fulfil the monitary ratio obtained. Therefore, the cooperative should increase the cash, net income (SHU) and the sale.